(untitled) (Al-Aasar, 2025)
Humorous Column writing flourished in Pakistan after independence. Its basic reason was the flawed political policies in connection with governmental decision making, which people soon realised in the wake of independence as multiple political parties divided the nation. Society’s friction, political and social problems, tragedies, events and economic changes were highlighted sarcastically by the column writers through the lens of national journalism. The purpose of such humorous columns was awareness of the masses. Prominent among such writers are Maulana Abdul Majeed, Abdul Majid Darya Abadi, Ibn e Insha, Charagh Hassan Hasrat, Ahmed Nadeem Qasmi, Mukesh Hyderabadi, Naqara Hyderabadi, Qazi Abdul Ghaffar, Haji Laq Laq, Muzaffar Ehsani, Hameed Nizami, Amjad Islam Amjad, Shoukat Thanvi, Intazar Hussain, Dr. Younas Butt, Mustansar Hussain Tarar, Atta-ul-Haq Qasmi, Munir Ahmed Qureshi (Muno Bhai), Nasrullah Khan, Hassan Nisar, Tahir Masud, Mujib ur Rehman Shami, Ashfaq Virk and the undersigned. One such columnist is Zafar Iqbal, who has respectable stature in the field of journalism not only for his humorous column writing but for his poetry as well. He has equal command over column writing and poetry. Zafar Iqbal started his poetry in 1962 through the creation of “Aab e Rawan” but his columns started to appear from 1974.